The role of sensory parameters in predicting clinical outcome after lumbar discectomy - Tampin, B.; Lind, C.; Slater, Helen (Georg Thieme Verlag, 2016)
Background: Lumbar discectomy is considered a safe, efficacious and cost-effective treatment for selected cases of patients with leg pain associated with the presence of a disc protrusion. But despite technically successful surgery, 30 % of patients complain of persistent pain on long-term follow up. Identification of possible predictors for a negative outcome is important, in the search for appropriate pre- and/or post-operative care and prevention of persistent disability. There is some evidence in the literature that quantitative sensory testing (QST) measures may play a role in prediction of patients’ pain persistency, however, this has never been investigated in patients undergoing lumbar discectomy.